Práticas culturais LGBTQIA+ fóbicas e racistas e o impacto na saúde mental da população LGBTQIA+ negra: uma revisão de literatura - Shimabukuro, Fabiana Harumi (2022)
This study aimed to conduct a systematic review of empirical studies that evaluated how coercive cultural practices targeting sexual and gender minorities, in association with racism, may affect these individuals’ mental health. Racism and LGBTQIA+phobia are topics that have been scarcely studied by Behavior Analysis. However, as scholars based on this theory aim to predict and control human behavior, it becomes important to investigate the variables involved in prejudice arising from the overlap of sexual orientation and gender and race identity. The identification of these variables would be a first step towards intervening in coercive cultural practices. The results obtained from the analyzed articles showed that the emergence of psychiatric disorders is strongly related to coercive practices, regardless of topography. This study can contribute to a greater visibility of the problem, promoting discussions about and, consequently, favor reducing the vulnerability of LGTBQIA+ people of color